2010
DOI: 10.1158/0008-5472.can-10-2956
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroblastoma-Associated F1174L ALK Mutation Causes Resistance to an ALK Kinase Inhibitor in ALK-Translocated Cancers

Abstract: The ALK kinase inhibitor crizotinib (PF-02341066) is clinically effective in patients with ALK-translocated cancers, but its efficacy will ultimately be limited by acquired drug resistance. Here we report the identification of a secondary mutation in ALK, F1174L, as one cause of crizotinib resistance in a patient with an inflammatory myofibroblastic tumor (IMT) harboring a RANBP2-ALK translocation who progressed while on crizotinib therapy. When present in cis with an ALK translocation, this mutation (also det… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
260
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(273 citation statements)
references
References 24 publications
10
260
1
Order By: Relevance
“…S6) and lies in a hydrophobic cluster composed by F1098, F1271, and F1245. Mutations involving F1174 were recognized as activating in neuroblastoma and phenylalanine substitution with a leucine was found in an IMT patient that relapsed after Crizotinib treatment (24). Clones carrying cysteine, valine, or isoleucine in residue 1174 instead of phenylalanine were selected at AP26113 100 nmol/L and 200 nmol/L in a previous Ba/F3 screen (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S6) and lies in a hydrophobic cluster composed by F1098, F1271, and F1245. Mutations involving F1174 were recognized as activating in neuroblastoma and phenylalanine substitution with a leucine was found in an IMT patient that relapsed after Crizotinib treatment (24). Clones carrying cysteine, valine, or isoleucine in residue 1174 instead of phenylalanine were selected at AP26113 100 nmol/L and 200 nmol/L in a previous Ba/F3 screen (34).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite great success, as expected from previous experience with tyrosine kinase inhibitors (TKI; refs. 21,22), the first cases of relapse due to the positive selection of mutant clones have already been detected in several Crizotinib-treated NSCLC and ALCL patients (20,(23)(24)(25)(26). To effectively overcome Crizotinib resistance, the development of second-generation ALK inhibitors is exponentially growing (27).…”
Section: Introductionmentioning
confidence: 99%
“…EML4-ALK-positive NSCLC represents another tyrosine kinasedriven cancer that is highly responsive to TKI therapy. Recently, two studies have reported the identification of secondary resistance mutations within the ALK TK domain in patients who relapsed on crizotinib (23,33). One of the mutations identified was the gatekeeper L1196M substitution, analogous to T315I in ABL and T790M in EGFR (23).…”
Section: Discussionmentioning
confidence: 99%
“…As with the ALK fusion proteins, the neuroblastoma activating mutants are amenable to inhibition by small molecule inhibitors of the ALK kinase activity, although differential sensitivity has been observed depending on the particular inhibitor and mutant (33,35). Interestingly, the F1174L variant and the related F1174C variant have been independently identified in the clinic as a mutations conferring resistance to crizotinib treatment (36,37).…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%